KEMAMPUAN BERPIKIR TINGKAT TINGGI (HOTS) TENTANG LINGKUNGAN BERDASARKAN LATAR BELAKANG AKADEMIK SISWA - Nur Choerun Nisa; Nadiroh Nadiroh; Eko Siswono (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2018)
The objectives of this research is try to finding out the information about the effect of academic background of students on the ability of high-level thinking (HOTS) in the environment. An ex post facto method has been applied by involving n= 120 students at SMA Negeri 21 Jakarta. Data was analyzed by Paired Sample T-tes. The results revealed that there were significant differences of student’s HOTS who come from academic background of MIA (Mathematics of Natural Sciences) and the academic background of IIS (Social Sciences). Therefore, to be considered about academic background factors that can lead students to improve HOTS in the environment. Further research on other variables that can influence HOTS in the environment, the background of respondents not only on the students but can be done to the general public because the environment to be the obligation of all the inhabitants of the earth. Environment has become the dominant issue in the beginning of this century, we need to re-educate our thinking, with further possibility to rekindle our hope of a future with dignity for all.